A xanthurenate and an isoindolinone from the mycelia of Hericium erinaceum. (August 2018) - Lin, Chwan-Fwu; Shiao, Young-Ji; Chen, Chin-Chu; Tzeng, Tsai-Teng; Chen, Chien-Chih; Lee, Li-Ya; Chen, Wan-Ping; Shen, Chien-Chang
Graphical abstract: Highlights: A xanthurenate and a new isoindolinone were isolated from the mycelia of Hericium erinaceum . The structures were elucidated by spectroscopic analysis including 1D, 2D NMR and MS. The isolated xanthurenate was found to possess a significant inhibition on the production of NO in LPS-activated microglia. Abstract: Ethyl 8-hydroxy-4-methoxyquinoline-2-carboxylate (1 ) and a new compound, erinacerin U (2 ), were isolated from the mycelia of Hericium erinaceum . Their structures were elucidated by spectroscopic analysis. Compound 1 was found to possess a significant inhibition on the production of NO in LPS-activated microglia.